Sugar-sweetened beverage purchases in urban Peru before the implementation of taxation and warning label policies: a baseline study - Caitlin M. Lowery; Lorena Saavedra-Garcia; Francisco Diez-Canseco; María Kathia Cárdenas; J. Jaime Miranda; Lindsey Smith Taillie (BMC, 2022)
Abstract Background Sugar-sweetened beverage consumption is associated with obesity and chronic disease. In 2018, Peru increased the tax on high-sugar beverages (≥6 g of sugar per 100 mL) from 17 to 25%, yet little is known about pre-existing beverage trends or demographic characteristics associated with purchases in the country. The aim of this study was to explore beverage purchasing trends from 2016 to 2017 and examine variation in purchase volume by sociodemographic characteristics among urban households in Peru. Methods This study used monthly household purchase data from a panel of 5145 households from January 2016-December 2017 from Kantar WorldPanel Peru. Beverage purchases were categorized by type and tax status under the 2018 regulation (untaxed, lower-sugar taxed, high-sugar taxed). To assess beverage purchasing trends, per-capita volume purchases were regressed on a linear time trend, with month dummies for seasonality and clustered standard errors. Mean volume purchases by beverage tax status (total liters purchased per month), overall and by key demographic characteristics (education, socioeconomic status, and geographic region), were calculated. Mean volume by beverage type was assessed to identify the largest contributors to total beverage volume. Results The trends analysis showed a decline in total beverage volume of − 52 mL/capita/month (95% CI: − 72, − 32) during the 24-month study period. Over 99% of households purchased untaxed beverages in a month, while > 92% purchased high-sugar taxed beverages. Less than half of all households purchased low-sugar taxed beverages in a month and purchase volume was low (0.3 L/capita/month). Untaxed beverage purchases averaged 9.4 L/capita/month, while households purchased 2.8 L/capita/month of high-sugar taxed beverages in 2017. Across tax categories, volume purchases were largest in the high education and high socioeconomic (SES) groups, with substantial variation by geographic region. The highest volume taxed beverage was soda (2.3 L/capita/month), while the highest volume untaxed beverages were milk and bottled water (1.9 and 1.7 L/capita/month, respectively). Conclusions Nearly all households purchased high-sugar taxed beverages, although volume purchases of taxed and untaxed beverages declined slightly from 2016 to 2017. Households with high SES and high education purchased the highest volume of taxed beverages, highlighting the need to consider possible differential impacts of the tax policy change by sub-population groups.